Impact of depression and social support on nonadherence to antipsychotic drugs in persons with schizophrenia in Thailand - Sirijit Suttajit; Sutrak Pilakanta (Patient Preference and Adherence, 2010)
Sirijit Suttajit, Sutrak PilakantaDepartment of Psychiatry, Faculty of Medicine, Chiang Mai University, Chiang Mai, ThailandBackground: Little is known about the effect of social support on nonadherence in persons with schizophrenia, especially in developing Asian countries where social support is considered to be imperative. Additionally, the role of depression as a mediator in the association between social support deficits and nonadherence has not been evaluated.Methods: This was a cross-sectional study conducted in 75 participants at a university hospital in Thailand. Logistic regression was used to determine whether depression and a deficit in social support were associated with nonadherence, and whether depression mediated this association.Results: There were strong relationships between nonadherence and major depressive episodes (odds ratio [OR] 9.5, confidence interval [CI] 2.3–38.9), living alone (OR 21.8, CI 3.5–143.0), and dissatisfaction with support from family (OR 10.0, CI 1.9–53.1). The OR of the association between social support deficits and nonadherence decreased by nearly one half after adjusting for depression.Discussion: Depression and social support deficits were significantly associated with nonadherence in persons with schizophrenia. Depression is important in mediating the association between social support deficits and nonadherence. Enhancing social support, as well as early detection and effective intervention for depression should be emphasized in interventions to improve adherence in persons with schizophrenia.Keywords: nonadherence, schizophrenia, depression, social support, antipsychotic drugs